Estudio introductorio. Relaciones históricas hispano-estadounidenses: visiones del siglo XX en clave cultural - Hilton, Sylvia L. (Revista Complutense de Historia de América, 2010)
This study presents a dossier which analyzes diverse manifestations of the role of culture in contemporary relations between Spain and the United States, as a contribution to current historiographical approaches to international cultural relations. Spanish publications on this subject are relatively scarce, so the introductory essay aims to review the historiographical context in which the research has been produced, before commenting on each article and author of the dossier. It offers an overview of what has been published in Spain since 1999 on Spanish-U.S. cultural relations. It finds that the main approach of the majority of the published studies has been the documentation and analysis of perceptions of the ‘other’, and it identifies the specific subjects that have appeared under two broad headings: Spain as seen by the USAmericans, and the United States in Spanish perceptions.